2006
DOI: 10.1161/01.res.0000233315.38086.bc
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Cells Undergo Telomere-Based Senescence in Human Atherosclerosis

Abstract: Abstract-Although human atherosclerosis is associated with aging, direct evidence of cellular senescence and the mechanism of senescence in vascular smooth muscle cells (VSMCs) in atherosclerotic plaques is lacking. We examined normal vessels and plaques by histochemistry, Southern blotting, and fluorescence in situ hybridization for telomere signals. (VSMCs), and intracellular and extracellular lipids. Plaque disruption results in acute myocardial infarction and stroke, whereas repeated rounds of subclinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
443
1
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 548 publications
(479 citation statements)
references
References 50 publications
21
443
1
14
Order By: Relevance
“…Evidence for telomere shortening in VSMCs has been provided by Matthews et al (2006), who also showed that telomere shortening in VSMCs was closely associated with increasing severity of atherosclerosis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Evidence for telomere shortening in VSMCs has been provided by Matthews et al (2006), who also showed that telomere shortening in VSMCs was closely associated with increasing severity of atherosclerosis.…”
Section: Discussionmentioning
confidence: 93%
“…This implies that senescent VSMCs may persist in vivo long enough to be of physiological significance in the pathogenesis of vascular disease. However, it has been reported that apoptosis is a feature of advanced atherosclerosis and this could promote telomere shortening (and thus senescence) by reducing the number VSMCs capable of replication (Matthews et al, 2006). Apoptosis in this instance is likely related to disease specific changes, such as an increase in oxidative stress, which is not normally observed during cell culture.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In vitro, accumulation of prelamin A can cause nuclear morphology defect, premature senescence and failure to repair DNA (39)(40)(41). In vascular diseases, accumulation of prelamin A accelerates senescence in atherosclerotic plaques by interfering with DNA damage repair and mitosis (42). Dysfunctions of vascular endothelial and smooth muscle cells were also shown to be related to prelamin A accumulation at the cellular and nuclear levels (39,43,44).…”
Section: Discussionmentioning
confidence: 98%
“…Было показано, что при атеросклерозе в гладко-мышечных клетках сосудистой стенки отмеча-ется значительное уменьшение длины теломер и снижение активности теломеразы по сравне-нию с данными даже в клетках из непоражен-ных участков того пациента. Одной из главных причин этих изменений, по-видимому, является негативной влияние реактивных кислородных субстанций на активность теломеразы в клетках, помимо их повреждающих ДНК эффектов [30].…”
Section: клеточный геном в патогенезе основных заболеваний 2010 т 1unclassified